Exploring the role of a semi-automated ultrasound technology in rural Indian antenatal care - Gururaj, A (2017)
Background: Although obstetric ultrasound is an integral, well-established component of antenatal care (ANC) in high income countries (HICs), women in low-and-middle income countries (LMICs) still face barriers to accessing the technology, e.g. cost and the lack of trained personnel. Most of the evidence for routine obstetric ultrasound has been gathered in HICs and does not necessarily reflect LMIC settings, such as India. The aim of this thesis, therefore, was to take a user-centred approach to understanding: (1) the use and utility of obstetric ultrasound in the primary health care pathway in rural India and (2) the value of semi-automated ultrasound technology in addressing gaps in access to early, high-quality examinations for pregnant women. Methods: A scoping pilot phase was first undertaken with stakeholders across the public health system in rural India and consisted of informal interviews that helped to inform study design. Following the pilot phase, qualitative in-depth interviews were conducted with 25 Primary Health Centre (PHC) doctors, Auxiliary Nurse Midwives (ANMs) and government officials in two rural districts in Andhra Pradesh and Haryana. Interviews were analysed using framework analysis, a type of thematic analysis approach. Results: Primary level care providers and government officials in both districts perceived ultrasound to be highly beneficial in the clinical management of obstetric problems. Specifically, ultrasound was seen as a necessary tool for decision-making regarding referral practices for high-risk deliveries, given the limited resources available at the primary health level, though was not emphasised for accurate gestational age determination. Participants believed that many women face numerous barriers in accessing ultrasound scanning centres (such as cost, high patient loads, distance to travel and awareness) as machines and personnel are not available at the primary level. Although participants claimed that pregnant women had at least one ultrasound scan, there was little standardisation regarding the number or timing of scans. Most participants strongly preferred the idea of easy-to-use, basic screening through a semi-automated ultrasound machine at the PHC level to improve patient and care provider convenience and decrease the burden on higher-level centres. However, many also expressed concerns about additional workload, the potential of misuse for sex determination and the maintenance of high-quality diagnoses. Conclusions and implications: Care providers and government officials perceived ultrasound diagnoses as critical to deciding whether to refer women who might need high-risk support to higher-level centres that are often geographically removed. A low-cost, portable, semi-automated ultrasound machine operated by a PHC doctor would likely improve access to standardised, high-quality antenatal care for women in rural settings, provided it includes effective safety and security mechanisms, limits overburdening PHC doctors and ANMs, and is coupled with systems-level structures (e.g. referral pathways). Findings also suggest a strong need to re-evaluate the evidence base for routine obstetric ultrasound in rural LMIC settings and include more stakeholders in participatory, co-design approaches to innovation.